PENGEMBANGAN KURIKULUM INTEGRATIF ISLAM, LOKAL VALUE, INTERNATIONAL MINDEDNESS DI KINDY AFKAARUNA ISLAMIC SCHOOL - Novi Fatkhiyatul Muyassaroh; Suyadi Suyadi (AWLADY : Jurnal Pendidikan Anak, 2020)
AbstractThe curriculum is the basis of an educational institution in order to help the achievement of the objectives that have been set. The background of this research is that there is an innovation of curriculum development in Afkaaruna Islamic School of aligning the three elements of value, Islamic, local and international thinking. The purpose of this research is to know how the development of integrative curriculum used by the institutions. Methods This study included descriptive qualitative research with researchers as subjects, method of collecting data through observation, documentation and interview. Results from this study data showed that the curriculum in Kindy Afkaaruna Islamic School, referring to International Preschool Curriculum (IPC) collaborated curriculum with the curriculum Ministry of religionn (KEMENAG), synchronized to Afkaaruna Learning Pack (ALP) that cover English, al-Dirasah al-Islamiyyah, and local value.